Synthesis, Biological Evaluation, Molecular Docking and DFT Study of Potent Antileishmanial Agents Based on the Thiazolo[3, 2‐a]pyrimidine Chemical Scaffold. Issue 10 (12th March 2018) - Chaturvedi, Radha N.; Arish, Mohd; Kashif, Mohammad; Kumar, Varinder; Reenu,; Pendem, Krishnaiah; Rub, Abdur; Malhotra, Sunita
Abstract: A series of 20 compounds having thiazolo[3,  2‐ a ]pyrimidine chemical scaffold were synthesized and evaluated for their antileishmanial activity against promastigotes of Leishmania donovani . Amongst all, two compounds showed promising antileishmanial activity in comparison to other compounds. Inhibitory concentration 50% (IC50 ) was calculated as 42.1 μM and 25.1 μM with selectivity index of 8.3 and 6.05, respectively against Miltefosine (reference drug) 37.78 μM with selectivity index of 2.05. To confirm the target of the these molecules, we modelled Leishmania donovani Ca 2+ ion channel (LdCC) protein and performed the docking analysis of the best antileishmanial activity exhibiting inhibitors. The free energy of binding was observed as −10.2 and −9.6 kcal mol −1 in comparison to reference drug −6.2 kcal mol −1 . It also makes several hydrogen bonds with our conserved residue Ser1655, Tyr1598 and Asn927. Furthermore, several hydrophobic contacts were also observed within the pocket. Finally, computational work employing density functional theory (DFT) was also carried out to investigate the electronic properties of the synthesized compounds. The in vitro and in silico activities conclusively revealed that our lead compounds may be used as a novel therapeutics against leishmaniasis. Abstract : A novel series of compounds containing thiazolo[3,  2‐ a ]pyrimidine chemical scaffold were designed and synthesized and screened for their antileishmanial activity against leishmania donovani . One compound9 f, showed excellent antileishmanial activity with IC50 25.1 μM as compared to Miltefosine with IC50 37.78 μM. Molecular docking studies showed that LDCC‐9 f complex has highest binding affinity of −10.2 kcal mol −1 . DFT studies including HOMO/LUMO studies were also performed to explore the molecular properties of lead compound.